2017
DOI: 10.1093/cid/cix105
|View full text |Cite|
|
Sign up to set email alerts
|

Cytomegalovirus DNA Detection by Polymerase Chain Reaction in Cerebrospinal Fluid of Infants With Congenital Infection: Associations With Clinical Evaluation at Birth and Implications for Follow-up

Abstract: A positive hCMV-PCR result in CSF is associated with symptomatic cCMV and SNHL at birth. However, no differences in neuroimaging studies, plasma viral load, or outcomes at 6 months were found. These results suggest that hCMV-PCR in CSF may not be a useful prognostic marker in cCMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
1
11
0
5
Order By: Relevance
“…These findings have been replicated since then for amniotic fluid [70][71][72] and for urine [73][74][75] and blood at birth [70,74,76], and their association both with the risk of developing sensorineural hearing loss and other cCMV-associated sequelae have been studied. A positive determination of CMV DNA in the cerebrospinal fluid at birth has also recently been associated with symptoms in the cCMV-infected neonate [77]. The reason why viruria at birth correlates with cCMV disease in other organs but does not seem to cause kidney damage in cCMV-infected infants is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been replicated since then for amniotic fluid [70][71][72] and for urine [73][74][75] and blood at birth [70,74,76], and their association both with the risk of developing sensorineural hearing loss and other cCMV-associated sequelae have been studied. A positive determination of CMV DNA in the cerebrospinal fluid at birth has also recently been associated with symptoms in the cCMV-infected neonate [77]. The reason why viruria at birth correlates with cCMV disease in other organs but does not seem to cause kidney damage in cCMV-infected infants is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent viral replication in the inner ear structures may play a role [7,8], but testing such a hypothesis is challenging. The largest available series that retrospectively explored the role of CMV detection in the cerebrospinal fluid (CSF) failed to find a correlation between positive CMV CSF polymerase chain reaction (PCR) and longterm hearing and neurological outcomes [9]. Some studies suggested that higher blood viral load in early infancy may be associated with SNHL [8,10,11], but other studies have not identified such an association [12,13].…”
mentioning
confidence: 99%
“…Despite the wide range of clinical manifestations, the determinants that drive the observed symptomatology (or lack thereof) are largely unknown. Likewise, there are no factors, including blood CMV loads, that have shown to reliably predict the development of late-onset SNHL in both symptomatic and asymptomatic infants 9,[23][24][25][26][27] . Furthermore, although infants with symptomatic disease demonstrate higher rates of SNHL than those that are asymptomatic, the subsets within both symptomatic and asymptomatic infants who are at highest risk of developing SNHL are not well defined 28 .…”
Section: Discussionmentioning
confidence: 99%